Linking Intrapreneurial Risk-Taking to Academic Leaders’ Performance - Bakar, Muhammad Shukri; Ramli, Azahari; Mohd Saad, Rosli; Poespowidjojo, Donny Abdul Latief; Ibrahim, Najafi Auwalu (Serials Publications, 2017)
Although significant relationships have been recorded between the variables of individual-level risk-taking propensity and performance in many sectors, the effect of this relationship remains less studied particularly as it relates to the individual performance of academic leaders operating in public universities. Hence, this study is aimed to determine the significant effect of intrapreneurial risk-taking on its relationship to academic leaders’ performance in Malaysian public universities. A quantitative research design based on the questionnaire survey was used to collect data. A total of 246 usable responses were received from middle-level academic leaders of twenty public universities throughout the country. They mostly comprised of faculty deans, academic heads of department, directors of academic centre of excellence, and programme chairpersons. The findings revealed a significant and positive relationship between intrapreneurial risk-taking behaviour andperformance.